Análise da situação do consumo alimentar e do Índice de Massa Corporal (IMC) de adultos das capitais do Centro-Oeste e do Distrito Federal a partir de dados do VIGITEL (2008-2019) - Soares, Ana Karolina Ferreira (2021)
Current food consumption has been characterized by a high caloric diet, with low satiety power, easy absorption and digestion and high amounts of sugars and sodium, contributing to the increasing occurrence of Chronic Non-Communicable Diseases (NCDs ), among them high rates of overweight and obesity, resulting in the possible impairment of the population's quality of life. Objective: To analyze the temporal trend of the situation of food consumption and Body Mass Index (BMI) in adults in the capitals of the Midwest and the Federal District, based on data from VIGITEL (2008-2019). Methods: This is a populationbased time series study with adults (≥ 18 years old), residing in the capitals located in the Midwest Region (Cuiabá, Campo-Grande, Goiânia and Brasília), based on the data obtained of the VIGITEL system in the years 2008 to 2019. The following variables were used in relation to food consumption: consumption of fruits and vegetables regularly (consumption of five or more servings daily), consumption of meat with excess fat (consumption of red meat with fat or chicken with skin without removing the visible fat from the food), consumption of beans regularly (consumption on five or more days a week) and consumption of soft drinks/artificial juices (consumption on five or more days a week); and overweight (BMI≥25 kg/m²) and obesity (BMI≥30 kg/m²) present in the VIGITEL survey. Regarding the independent variables, gender, age groups, years of education and marital status were considered. Regarding the statistical analysis, the prevalences of the dependent variables were calculated, as well as their respective 95% confidence intervals for each year analyzed. For the analysis of temporal trend, the PraisWinsten procedure was performed, using the Stata 13 program for data analysis. In all statistical tests, a significance level of 5% was considered. Results: No significant trends were obtained in relation to the consumption of fruits and vegetables. There was a decreasing trend in the consumption of meats with excess fat in the capitals of Cuiabá (-1.41%) and Goiânia (-4.61%), among male adults (-2.74%), aged 40- 59 years (-5.73%), individuals with 0-8 years of education (-3.45%) and with 9-11 years of education (-1.91%), and between widowed and separated adults (-7 .42%) or divorced (-6.34%). There was also a decreasing trend, for all variables studied, in relation to the consumption of soft drinks and artificial juices, with the exception of widows who were evaluated as stationary. Decreasing trends were found in the regular consumption of beans in the cities of Cuiabá (-2.40%) and Goiânia (-2.83%), adults aged between 40 and 59 years (-4.33%), with 0 to 8 years of schooling (-2.26%), those married or in a stable relationship (-4.18%) showed a decreasing trend in the analyzed period. Regarding the anthropometric profile, in all the cities evaluated, there was an increasing trend in BMI, as well as the independent variables, with the exception of widows who presented stationary results. Conclusion: Changes were identified in the sociodemographic profile of the population residing in the Midwest Region, as well as in the indicators of food consumption considered and BMI. Favorable changes occurred in food consumption in relation to the consumption of meat with excess fat and consumption of regular soft drinks and artificial juices, but the results did not reach that the observed reductions related or are sufficient to stop the significant increase in the prevalence of excess weight and obesity.